Penguatan Ekonomi Orang Tua pada Keluarga Anak Jalanan (Studi Kasus: Sanggar Alang-Alang Surabaya) - Puji Sucia Sukmaningrum,; Siti Inayatul Faizah, (Jurnal Sosial Humaniora, 2025)
The aim of this study is to find out the strategy on how to strengthen the economy welfare of street children’s family in Surabaya. Children are the next generation of the nation whose all their needs should be fulfilled. Surabaya as one of the largest cities in Indonesia has some issues relating to poverty and street children. The research employed qualitative research method and the informants were the street children in Sanggar Alang-Alang Surabaya. The result of the research showed that the strategy that can be given to parents of the street children is the construction of the family workforce through creative economy programme, protection from discrimination against their work, provision of services, and creating productive business for poor families.